Family conflicts between parents and young children (Journal of Parents and Teachers, 2013)
Most problems among adolescents are due to changes that are associated to this transitional stage. Frequently, these changes have a negative impact living with their families. However, everybody thinks that once the children start going to college or working, these conflicts will banished. Nevertheless, current studies reveal that this thought does not always correspond with the reality. With young children arguments are still an issue. This article talks about the families that still live with young children and the factors that best influence in a good family environment. Throughout the piece of writing, it is highlighted that it is not important how much time passes by, but how close people gets, how flexible, you, as a member of your family are, and how good you communicate with the rest of your family members.
Keywords: Family environment; life cycle; Communication; Affectivity and feeling; family counseling